Evaluation of selected agricultural by-products as potential feeds for rearing edible grasshopper, Ruspolia differens (Serville) (Orthoptera: Tettigoniidae) - Amos Acur; Geoffrey Maxwell Malinga; Philip Nyeko (CABI Agriculture and Bioscience)
Abstract Background Crop residues and agro-industrial by-products constitute an enormous pool of unused and often neglected resources that could be productively utilized for rearing edible insects to meet the global demand for animal-based protein. Utilizing such products as feedstocks can lower the cost of edible insect production and reduce associated environmental pollution. Methods We evaluated the biology (survival, developmental duration, and adult fresh weight) of Ruspolia differens reared on eleven locally available agricultural by-products in Uganda, namely; dry maize cob, waste from a locally brewed finger millet drink, cotton seed cake, soybean hull meal, sunflower cake, pumpkin pulp, peelings of unripe banana, cassava, sweet potato, pineapple and pumpkin. Germinated finger millet was used as a control. Newly hatched (1 day old) nymphs were reared individually on each diet until 14 days post adult emergence. The nutritional profiles of the by-products were also determined. General linear models were fitted to analyse whether R. differens performance differed between sexes and among diets. The relationship between R. differens performance and the nutritional profiles of the diets were tested by Pearson correlation coefficient. Results Only three test diets (soybean hull meal, dry maize cob, and the local brew waste) supported survival till the adult stage. Nymphal survival negatively correlated with diets’ crude fibre content (r = − 0.96, p = 0.042). Nymphal development duration significantly differed among the diets, with the shortest duration under soybean hull meal (approx. 138 days) and the longest under the local brew waste (205 days). Nymphal development duration positively correlated with diets’ crude fibre content (r = 0.95, p = 0.022). Adult fresh weight at emergence and 14 days post emergence did not differ across the test diets. Female individuals were ~ 1.3 times heavier than males 14 days post emergence, although both sexes had similar weights at adult emergence. The levels of secondary metabolites in the diets were not associated with any growth performance parameters of R. differens. Conclusions Our findings suggest that R. differens can thrive and develop on some agricultural by-products. The results could guide the design of R. differens mass-rearing programs using locally available agricultural by-products.